Structural Challenges Of The International System And The Us Security Strategies In Afghanistan - Farhad Ghasemi, Sayed Taher Erfani (International Journal of Modern Agriculture, 2021)
Afghanistan has always been at the center of competition between the great powers due to its geopolitical position in the world order and its active power cycle, experiencing severe interferences concerning its internal affairs. The policies of the great powers towards Afghanistan have always been affected by the rivalry in the global cycle of power and the structural challenges of the international system caused by the existence of such a cycle. Developments in the international system, especially after the Cold War and the collapse of the Soviet Union, have caused Afghanistan to be one of the pillars of US regional policy. In addition, with the recreation of Russian power and the rise of China as well as the formation of the transition period in the world order, the international system has shown structural challenges regarding the United States. With regards to the two great powers of the international system _Russia and China- challenging American hegemony in Afghanistan as well as the presence of US forces in this country, Afghanistan has turned into one of the connection centers of structural pressures related to the international system and geopolitical currents – which is being a response to such pressures. Accordingly, the research question is based on the structural pressures of the international system and US security strategies in Afghanistan. The present study regards Afghanistan as a geopolitical center by which part of the dynamic control of the power of the challenging countries is realized. Through the link between the global order and the geopolitics of Afghanistan, this study seeks to explore one of enduring problems of Afghanistan – i.e. the security strategies of the great powers- and to present a new research agenda in the field of the great powers and Afghanistan.